The Concept 'Patient Satisfaction' as it Relates to Contemporary Health Care - Ekram, ARM Saifuddin; Rahman, Md Fazlur (TAJ: Journal of Teachers Association, 2009)
doi: 10.3329/taj.v19i1.3159 TAJ 2006; 19(1)